'Food spoilage indicator' / Muhammad Hazwan Ab Hamid, Raudhah 'Aqilah Rahimie and Suriana Abdullah - Ab Hamid, Muhammad Hazwan; Rahimie, Raudhah 'Aqilah; Abdullah, Suriana (2017)
The team is developing a 'Food Spoilage Indicator', a small and portable device used to measure pH, water activity, texture, and color of food. This device is the combination of complex and expensive instruments available in the food industry. The new product will be a simpler device that provides and combines several functions of those instruments at lower cost. This device is also able to determine the level of freshness and safety of the food to be eaten.